Single nucleotide polymorphism (SNP) diversity of cassava genotypes in relation to cassava brown streak disease in Mozambique - Oyesigye, E.; Zacarias, A.; Mondjana, A.; Magaia, H.; Ferguson, Morag E. (Cambridge University Press, 2018)
Cassava brown streak disease (CBSD) remains a major threat to cassava production in Mozambique. Breeding for CBSD resistant varieties that are also preferred by farmers is an integral part of managing the disease. The main objective of the study was to determine the genetic relationship between farmer-preferred varieties from Mozambique with those from Tanzania whose resistance to CBSD is known and some of which are being used as parents in quantitative trait loci (QTL) detection studies. To achieve this, 103 genotypes collected from farmers’ field in three provinces of Mozambique were genotyped together with five varieties from Tanzania whose CBSD response is well known. Thirty-five single nucleotide polymorphism (SNP) markers with a high minor allele frequency in East African landraces were used. Results indicated that seven Mozambican genotypes were genetically similar to either one of the four Tanzanian CBSD resistant genotypes while Xino Nn'gole was genetically identical to Namikonga a CBSD resistant variety, based on the SNPs used here. Little genetic differentiation was observed in cassava between provinces, with the majority of genetic variation distributed within individual genotypes (98%) rather than among provinces (2%). Both observed (Ho) and expected (He) heterozygosity in three provinces were generally high (Ho = 0.496) and (He = 0.455). There is a high likelihood that the eight genotypes similar/identical to those from Tanzania may share the same QTL associated with CBSD resistance thus should be further evaluated for agronomic traits as well as response to CBSD.